Overall and sexual quality of life in women with breast cancer during and after oncologic treatment: a review - Chałubińska, Justyna; Łuniewska-Bury, Jolanta; Spych, Michał; Fijuth, Jacek (Menopause Review/Przegląd Menopauzalny, 2010)
The definition of quality of life is derived from the WHO’s general definition of health and reflects coping with normal stress, productive work and social functioning. Assessing quality of life in clinical trials is of crucial importance. Implications of medical interventions have to be evaluated not only in terms of hard endpoints (e.g. death, overall survival etc.) but also soft ones like for instance sexual functioning. The importance of assessing quality of life is sometimes underestimated in clinical trials and in everyday clinical practice. The purpose was a survey of current literature in the field of quality of life in breast cancer patients and survivors. The authors paid special attention to the sexual aspects of quality of life. The article outlines the influence of various demographic factors such as age, marital status, educational level and race on quality of life scores in breast cancer patients. The authors elucidated the differing impact of the type and stage of treatment (surgery, reconstruction, systemic therapy and radiotherapy) on quality of life in the group described above. Within this article the readers will also find information about quality of life in breast cancer patients in subsequent years after finalization of treatment. The relation of psychiatric disorders, more common in cancer patients, and their treatment with general and sexual quality of life is also presented and discussed. The readers will find the information contained in this article as a current review of quality of life literature and guidelines which could be incorporated into routine medical care.